Microbial consortium culture and vermi-composting technologies for recycling on-farm wastes and food production - Girish Chander; Suhas P. Wani; S. Gopalakrishnan; Ankita Mahapatra; Swati Chaudhury; C. S. Pawar; Manoj Kaushal; A. V. R. Kesava Rao (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose A study was conducted to characterize the ‘Madhyam culture’ (Excel Crop Care Limited.), an aerobic-composting microbial consortium culture, and understand composting dynamics, product quality and use in crop production vis-à-vis vermi-composting (using earthworms). Methods 16S rDNA analysis was used to characterize aerobic-composting culture. Aerobic-composting and vermi-composting technologies were evaluated to decompose sorghum straw and dung biomass (80:20 ratio; primed with 0.5% urea and 4% rock phosphate) to study days to maturity and composting dynamics in terms of changes in temperature and microbial population. Compost quality was tested for macro-, micro-nutrients and C:N ratio, and evaluated for food production in on-farm trials. Results 16S rDNA analysis screened sixteen bacterial isolates—eight related to genus Bacillus, three to each Halobacillus and Staphylococcus, one to each Microbacterium and Streptomyces. The population of bacteria was 4.5 cfu ml−1 at 10−7 dilution. Aerobic- and vermi-composts matured in around 50 and 60 days, respectively. Aerobic-composting throughout recorded relatively higher bacterial population, and higher temperatures during the initial phase. Aerobic-compost tested for high nutrient (1.55% N, 0.93% P, 1.00% K) content and stable C:N ratio (10.3) compared to vermi-compost (1.11% N, 0.43% P, 0.96% K and C:N ratio of 11.7). Field evaluation of both composts showed yield benefit and saving of chemical fertilizers up to 25%. Conclusions Aerobic-composting (using microbial consortium culture), like vermi-composting, proved to be an effective technology with advantage of no requirement to maintain ambient living conditions in lean periods as is required for earthworms in vermi-composting, but needs more energy/labor for biomass turnings.